(untitled) (Eureka Journal of Computing Science & Digital Innovation, 2026)
In this research work, the effectiveness of embeddings generated using the DistilBERT model based on deep learning and classical machine learning algorithms in the process of automatic text classification was comparatively studied. Within the framework of the research, Logistic Regression, Ridge Classifier, Linear SVC, SGD Classifier and Random Forest models were tested on selected categories of the 20 Newsgroups dataset. The texts were converted into contextual vectors using the transformer model and then transferred to classical classification algorithms. The analysis was carried out based on the accuracy level of the models, the F1 index and the training and testing times. The results of the research showed that transformer-based embeddings increase the effectiveness of classical machine learning models.